Motivasi Kerja sebagai Pondasi Peningkatan Kapabilitas Profesional Guru - Alfaniah, Afifi; Rindaningsih, Ida (Lembaga Yasin AlSys, 2025)
The purpose of this study is to analyze the role of work motivation as a foundation for improving teachers' professional skills. Work motivation is recognized as an internal factor that encourages teachers to participate in the learning process and encourage innovation, which directly affects the quality of education students receive. The method used is a literature review, which examines various relevant journals and previous research. This research shows that work motivation not only helps maintain morale, but becomes the main driver to achieve optimal results at work. In addition, the study found that teachers' personal and professional development complement each other in their professional development. Motivated teachers are more likely to actively participate in training and development programs, which helps them improve their performance and performance. This study concludes that to improve teachers' professional skills, educational institutions need to create a supportive work environment, reward performance and provide training and development opportunities. Therefore, increasing teachers' work motivation is expected to contribute to the progress of education in Indonesia and improve the quality of human resources in the field of education.